Pengaruh Mobilisasi Dini Terhadap Nyeri Pasca Operasi di RSD K.R.M.T Wongsonegoro Semarang - Maharani Shalma Rosalina; M. Jamaluddin (Jurnal Rumpun Ilmu Kesehatan, 2024)
Background: Pain is the reason most frequently complained by patients to seek help from a health facility and this condition almost always indicates a disease condition or pathological process. Surgery as one of the causes of pain is an invasive medical procedure used to diagnose or treat disease, injury or body deformity. Objectives: To determine the effect of early mobilization on reducing the pain scale in post-operative patients at K.R.M.T Wongsonegoro Hospital Semarang. Methods: This type of research is descriptive research in the form of a case study in November 2023 at K.R.M.T Wongsonegoro Hospital Semarang. The sample was 2 post-operative patients. Data analysis by changing the data obtained in narrative form and interpreting the results. Findings: In the first respondent, after early mobilization for 3 days, the pain scale decreased from scale 6 (moderate pain) to scale 2 (mild pain), in the second respondent, before early mobilization for 3 days, the pain scale decreased from scale 7 (severe pain) to scale 3 (mild pain). Implications: provide information for nurses and future researchers regarding early mobilization as a development of nursing interventions to reduce postoperative pain